Regionalism reconsidered : the Economic Commission for Africa - Gruhn, Isebill V. (Boulder, Colo. : Westview Press, 1979)
This book is on economic commission for Africa during the 1966 and 1976
Includes index.
Includes bibliographical references: p. 148-151.
oo 20/09/2018
Loans
Keywords: Regionalism; Economic integration; Africa